Importance of hydrogen migration in catalytic ammonia synthesis over yttrium-doped barium zirconate-supported ruthenium nanoparticles: visualization of proton trap sites - Foo, C; Fellowes, J; Fang, H; Large, A; Wu, S; Held, G; Raine, E; Ho, P-L; Tang, C; Tsang, SCE (American Chemical Society, 2021)
Barium zirconate perovskites have been systematically investigated as protonic supports for ruthenium nanoparticles in the Haber-Bosch ammonia synthesis reaction. A series of supports based on barium zirconate were synthesized, for which the B-site of the ABO3 perovskite was doped with different aliovalent acceptor cations and in varying ratios, resulting in varying proton conductivities and trapping behaviors. Crucially, we provide direct evidence of the importance of a hydrogen-migration mechanism for ammonia synthesis over these proton-conducting materials from the studies of reaction kinetics, in situ X-ray photoelectron spectroscopy, and neutron powder diffraction (NPD), which requires the proper balance of oxygen vacancy concentration (B-site doping), trapping-site concentration, and proton-hopping activation energy. We report evidence of a large dynamic coverage of OH groups on the support and the first visualization of both weak and strong proton trap sites within the perovskite lattice through the use of NPD.